Photocurable methacrylate/nanosilica composites - Andrzejewska, E.; Sądej, M. (Polimery, 2022)
Two types of photocurable systems containing triethylene glycol dimethacrylate (TEGDM) and 3-15 wt. % of nanosilica were prepared and investigated. The silicas used were structure modified fumed silicas aftertreated by methacrylsilane. The obtained dispersions were characterized by mean particle size (Z-average diameter), polydispersity index (PDI), Zeta potential and by the viscosity of the system (?). It was found that the maximum polymerization rate Rpmax and double bond conversion p increase with silica concentration up to 5 or 4 wt. %, depending on silica type; further increase in silica content reduces both Rpmax and p. This result correlates well with the stability of the dispersion as measured by its Zeta potential value. The lowest Zeta potentials were obtained for composites showing the highest Rpmax values.